AN ERROR ANALYSIS OF THE TRANSFORMATION FROM DIRECT TO INDIRECT SPEECH - Idami, Zahratul (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2017)
The objective of the study is to reveal the types of errors made by students in transforming direct to indirect speech in the form of statements. Furthermore, it attempts to find out the kind of errors that the students do most. To achieve the objectives of the study, the writer conducted a field research in which a test of grammar was administered. Then she did the library research in order to find some books and references that were related to error analysis and grammar. The subjects of the study were the second grade students of SMA Negeri 2 Peusangan. There were 295 students from which 34 students were taken as the sample. With the intention of drawing representative sample, simple random sampling was applied. The data were in the form of students’ scores on the tests. The data shows that the students made errors on the selection of appropriate tenses, pronouns, and adverb of time. The most errors they made were in changing pronoun. In line with the result of the research, the writer suggested that to improve the students’ ability in transforming direct to indirect speech, students have to learn more about pronoun, tenses, and adverb of time in turning direct to indirect speech. Additionally, it is essential to the teacher to know that choosing the appropriate pronoun is still hard for the students, so that they have to find a new way to improve it.